Identification of Products of Tetrapyrrole Pathway - Hájek, Jan (Jihočeská univerzita, 2013)
Cultivation of a model cyanobacterium Synechocystis PCC 6803 under low light conditions in the presence of glucose and TES buffer leads to a change of the medium color from colorless to yellow. The absorption spectrum of the excreted unknown compound indicated a possible relationship to plant chlorophyll degradation products. To confirm this speculation the compound was purified by a combination of solid phase extraction and HPLC. The mass and NMR characteristics excluded its close relationship to modified tetrapyrroles, nevertheless the precise structure could not be determined by these means due to a complicated nature of the compound and its high polarity.
Identification of Products of Tetrapyrrole Pathway
Keywords: low light cultivation; TES buffer; tetrapyrrole pathway